2012
DOI: 10.1021/ja211658t
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nanoparticles Catalyzing the Asymmetric Transfer Hydrogenation of Ketones

Abstract: Investigation into the mechanism of transfer hydrogenation using trans-[Fe(NCMe)CO(PPh(2)C(6)H(4)CH═NCHR-)(2)][BF(4)](2), where R = H (1) or R = Ph (2) (from R,R-dpen), has led to strong evidence that the active species in catalysis are iron(0) nanoparticles (Fe NPs) functionalized with achiral (with 1) and chiral (with 2) PNNP-type tetradentate ligands. Support for this proposition is given in terms of in operando techniques such as a kinetic investigation of the induction period during catalysis as well as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
157
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(165 citation statements)
references
References 71 publications
8
157
0
Order By: Relevance
“…284 During mechanistic investigation of the catalytic activity of the i ron − P NNP complex t r a n s -[Fe (NC Me) CO-(PPh 2 C 6 H 4 CHNCHR−) 2 ][BF 4 ] 2 for TH of ketones, Morris found that the real active species formed during catalysis are iron(0) nanoparticles modified with achiral PNNP-type tetradentate ligands (Scheme 23). 285 This proposed mechanism was given strong evidence by various analyses such as in operando techniques, poisoning experiments, scanning transmission electron microscopy (STEM) imaging with energydispersive X-ray spectroscopy (EDX) analysis, X-ray photoelectron spectra (XPS) analysis, superconducting quantum interference device (SQUID) magnetometry analysis, and a polymer supported substrate experiment. 285 Other groups also reported crucial studies on iron−PNNPcatalyzed TH.…”
Section: Recent Advances and Trendsmentioning
confidence: 99%
“…284 During mechanistic investigation of the catalytic activity of the i ron − P NNP complex t r a n s -[Fe (NC Me) CO-(PPh 2 C 6 H 4 CHNCHR−) 2 ][BF 4 ] 2 for TH of ketones, Morris found that the real active species formed during catalysis are iron(0) nanoparticles modified with achiral PNNP-type tetradentate ligands (Scheme 23). 285 This proposed mechanism was given strong evidence by various analyses such as in operando techniques, poisoning experiments, scanning transmission electron microscopy (STEM) imaging with energydispersive X-ray spectroscopy (EDX) analysis, X-ray photoelectron spectra (XPS) analysis, superconducting quantum interference device (SQUID) magnetometry analysis, and a polymer supported substrate experiment. 285 Other groups also reported crucial studies on iron−PNNPcatalyzed TH.…”
Section: Recent Advances and Trendsmentioning
confidence: 99%
“…This constitutes a relatively rare example in which the poisoned catalyst has been detected as part of studies focused on determining the true active catalyst. 1,12 The poisoning data in Figure 4, when combined with the detection of the [Rh 1 Cp*Cl(1,10-phenanthroline)] + as the poisoned product, add considerable credence to the hypothesis of a Rh 1 Cp*-based species as the dominant catalyst in the 22°C and 2.7 atm initial H 2 pressure cyclohexene hydrogenation system investigated herein.…”
Section: Controls Of a Standard Conditions Cyclohexenementioning
confidence: 57%
“…Recently, Baratta and co-authors [11] found that 2-(aminomethyl) pyridine (ampy) accelerated the transfer hydrogenation (TH) of ketones [12][13][14] in Ru(II) and Os(II) complex catalysts. Very recently, Morris group [15,16] reported that chiral NNPP ligands and their iron(II) complexes were effective in the ATH of ketones under mild conditions, representing a rare case of using inexpensive iron as the active metal. Although new ligands and their transition metal complexes have been established in this area [17][18][19][20], the desire for more highly active catalytic systems with better stereoselectivity and broader substrate scopes under mild conditions is still strong.…”
Section: Introductionmentioning
confidence: 99%